The Hemi-Fontan operation: A critical overview - Sachin Talwar; Vinitha Viswambharan Nair; Shiv Kumar Choudhary; Balram Airan (Wolters Kluwer Medknow Publications, 2014)
The hemi-Fontan (HF) operation is a staging procedure in the journey towards an ultimate Fontan palliation. Although popular in the Western world, it has found limited application in the developing world. In this review we discuss the indications, techniques, merits, and demerits of this procedure along with its present day role in developing world where there is lack of awareness about this operation.